Ali posebnosti slovenskega poslovnega okolja vplivajo na delovanje in širitev podjetij s tujim kapitalom? - Jaklič, Andreja (IB revija (Ljubljana), 2010)
Slovenia has one of the lowest levels of inward foreign direct investment (FDI) penetration of any country. Recently, assessments of the countryćs potential attractiveness and its actual performance in attracting FDI show large and persistent gaps. Based on a sample of foreign investment enterprises, the paper analyses motives, integration in the host economy, barriers, satisfaction, economic policy measures, capabilities for international operations and investment plans of foreign investors in Slovenia. It then examines the impact of these factors on employment, sales and productivity growth of foreign investment enterprises. The main advantages of Slovenia as an investment location are long-term cooperation (developed in the pre-investment stage), and a high-quality labour force. However, availability of skilled employees is a problem. Most of the barriers faced by foreign investors have not been reduced in the period between investors'' entry to the market and 2008. The main deficiencies of the Slovenian business environment according to foreign investors are high taxes, payment arrears, high labour costs, problems in hiring and firing workers, and an inefficient legal system. Factors in the Slovenian business environment do not affect the growth and expansion of existing foreign investment enterprises.
Keywords: poslovno okolje; podjetja; neposredne tuje investicije; Slovenia; Slovenija; Das Kapital; kapital